Design, synthesis and evaluation of some N-methylenebenzenamine derivatives as selective acetylcholinesterase (AChE) inhibitor and antioxidant to enhance learning and memory - Shrivastava S.K.; Srivastava P.; Upendra T.V.R.; Tripathi P.N.; Sinha S.K. (My University, 2025)
Series of some 3,5-dimethoxy-N-methylenebenzenamine and 4-(methyleneamino)benzoic acid derivatives comprising of N-methylenebenzenamine nucleus were designed, synthesized, characterized, and assessed for their acetylcholinesterase (AChE), butyrylcholinesterase (BChE) inhibitory, and antioxidant activity thereby improving learning and memory in rats. The IC50values of all the compound along with standard were determined on AChE and BChE enzyme. The free radical scavenging activity was also assessed by in vitro DPPH (2,2-diphenyl-1-picryl-hydrazyl) and hydrogen peroxide radical scavenging assay. The selective inhibitions of all compounds were observed against AChE in comparison with standard donepezil. The enzyme kinetic study of the most active compound 4 indicated uncompetitive AChE inhibition. The docking studies of compound 4 exhibited the worthy interaction on active-site gorge residues Phe330 and Trp279 responsible for its high affinity towards AChE, whereas lacking of the BChE inhibition was observed due to a wider gorge binding site and absence of important aromatic amino acids interactions. The ex vivo study confirmed AChE inhibition abilities of compound 4 at brain site. Further, a considerable decrease in escape latency period of the compound was observed in comparison with standard donepezil through in vivo Spatial Reference Memory (SRM) and Spatial Working Memory (SWM) models which showed the cognition-enhancing potential of compound 4. The in vivo reduced glutathione (GSH) estimation on rat brain tissue homogenate was also performed to evaluate free radical scavenging activity substantiated the antioxidant activity in learning and memory. © 2017 Elsevier Ltd